2015
DOI: 10.5435/jaaos-d-14-00042
|View full text |Cite
|
Sign up to set email alerts
|

Management of Osteoporosis in Spine Surgery

Abstract: Osteoporosis is a burgeoning clinical problem that is characterized by decreased bone strength and density. It predisposes patients to fragility fractures and debilitating spine deformities. Several complications are associated with spine surgery in patients with osteoporosis, and there is currently no treatment algorithm to guide the spine surgeon. A multidisciplinary approach to treatment of patients with osteoporosis and spine deformity or fracture is encouraged, and preoperative planning is crucial for suc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
109
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 128 publications
(110 citation statements)
references
References 43 publications
0
109
0
1
Order By: Relevance
“…25,26 Spine surgery in patients with decreased bone mineral density has also been shown to be predisposed to pseudoarthrosis, adjacent level degeneration, progressive junctional kyphosis, and compression fractures, all of which might, but not necessarily, necessitate a revision procedure. 20,27 The finding that Medicare insurance status was more strongly associated with revision cervical spine surgery might be a reflection of the older age of Medicare patients and their generally higher comorbidities. 28 Urban hospitals were also found to have higher rates of revision cervical spine surgery.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…25,26 Spine surgery in patients with decreased bone mineral density has also been shown to be predisposed to pseudoarthrosis, adjacent level degeneration, progressive junctional kyphosis, and compression fractures, all of which might, but not necessarily, necessitate a revision procedure. 20,27 The finding that Medicare insurance status was more strongly associated with revision cervical spine surgery might be a reflection of the older age of Medicare patients and their generally higher comorbidities. 28 Urban hospitals were also found to have higher rates of revision cervical spine surgery.…”
Section: Discussionmentioning
confidence: 93%
“…It is reasonable to assume that options for adequate fixation become limited when patients with severe OS present for surgical consultation. 20 Surgeons might choose more complex constructs such as combined anterior-posterior fusion because they increase load sharing, decrease overall construct strain, and thus lead to increased stability. 20,21 Consequently, surgeons are not just treating the primary condition, but secondarily calculating the risk these patients have construct failure and future revision.…”
Section: Discussionmentioning
confidence: 99%
“…PMMA-augmented screw fixations and other technical modifications like long-segment constructs is considered to reduce the risk of instrumentation failure in osteoporotic patients (4,41,42). Multiple points of fixation have been recommended in the osteoporotic spine for a long time (43).…”
Section: Resultsmentioning
confidence: 99%
“…Because of complications associated with bisphosphonate use (including osteonecrosis of the jaw, serum calcium disruptions and renal impairment, and subtrochanteric femoral fractures), there is still no consensus on the use of these medications in managing osteoporosis. 45 PTH is also used to increase BMD and reduce fracture risk among high-risk patients. The animal studies [46][47][48] investigating PTH revealed that the therapy leads to increased fusion rate and improved fusion structure.…”
Section: Bisphosphonates and Parathyroid Hormonementioning
confidence: 99%